The p-adic Simpson correspondence and Hodge-Tate local systems - Abbes, Ahmed 1970-; Gros, Michel 1956- (Lecture notes in mathematics, 2024)
Preface -- An overview -- Preliminaries -- Local Study -- Global Study -- Relative cohomologies of Higgs-Tate algebras.Local Study -- Relative cohomology of Dolbeault modules -- References -- Index.